2016
DOI: 10.1001/jamaoto.2016.1089
|View full text |Cite
|
Sign up to set email alerts
|

Tracheotomy Outcomes in Super Obese Patients

Abstract: Tracheotomy in super obese patients is a safe and effective strategy for airway management. Critically ill, super obese patients have a high likelihood of remaining dependent on a tracheotomy or ventilator at the time of discharge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 19 publications
2
14
0
4
Order By: Relevance
“…Data from our cohort suggests that performing tracheotomies late (>10 days after intubation) does not affect 30‐day mortality, complications, or decannulation. Additionally, we did not find BMI to be predictive of complications or 30‐day mortality, which is consistent with research supporting the safety of tracheotomy in obese or even “superobese” patients with BMI ≥40 …”
Section: Discussionsupporting
confidence: 90%
“…Data from our cohort suggests that performing tracheotomies late (>10 days after intubation) does not affect 30‐day mortality, complications, or decannulation. Additionally, we did not find BMI to be predictive of complications or 30‐day mortality, which is consistent with research supporting the safety of tracheotomy in obese or even “superobese” patients with BMI ≥40 …”
Section: Discussionsupporting
confidence: 90%
“…They found that 44% of obese patients (BMI, 30 to 50 kg/m 2 ; n = 34) had undergone successful decannulation, a similar finding to the 50% of patients within this BMI range in the present study (n = 78) with successful decannulation. Only 6 patients in the present study had a BMI greater than 50 kg/m 2 compared with 31 patients in the study by Marshall et al 26 However, despite the small sample size, we found similar rates of long-term tracheostomy dependence, with 7% of the super morbidly obese patients progressing to decannulation in their study and 17% of these subjects progressing to decannulation in our study. A similar weakness of both studies was that the analysis was confined to the information available from each patient's medical records exclusively from the institution conducting the study; thus, the postdischarge clinical course of the patients discharged to health facilities was largely unknown.…”
Section: Discussionsupporting
confidence: 47%
“…Most reported obese tracheostomy studies did not evaluate the postoperative course of these patients, and, of the available studies, none discussed the downsizing process in any detail. A study by Marshall et al 26 assessed obese and super morbidly obese (BMI >50 kg/m 2 ) patients who had undergone tracheostomy. They found that 44% of obese patients (BMI, 30 to 50 kg/m 2 ; n = 34) had undergone successful decannulation, a similar finding to the 50% of patients within this BMI range in the present study (n = 78) with successful decannulation.…”
Section: Discussionmentioning
confidence: 99%
“…En esta serie de casos, el IMC resultó significativo para la presentación de complicaciones, lo cual coincide con lo reportado por otros autores, quienes han referido un riesgo significativamente mayor en los pacientes obesos (23)(24)(25) , sobre todo en el período intraoperatorio y postoperatorio temprano, especialmente en los que cuentan con un IMC igual o superior a 35 (26,27) . Además de los mencionados, los pacientes con intubación orotraqueal prolongada tuvieron mayor riesgo de resultados adversos, lo cual ha sido señalado por otros autores, quienes reportaron 1.42 veces más probabilidad de tener una complicación postoperatoria tardía en individuos intubados por más de una semana; por su parte, la relación que se distinguió en este estudio entre resultados adversos y el tipo de anestesia empleado, difiere de los hallazgos en otras investigaciones, donde no se identificaron diferencias (13) .…”
Section: Discussionunclassified